PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS VISUALISASI KOLONISASI METRO UNTUK MENINGKATKAN PEMAHAMAN SEJARAH LOKAL SISWA SMA - Anggi Widiastuti; Umi Hartati (UNIVERSITAS MUHAMMADIYAH METRO, 2020)
Learning history in this era is less liked by students. With learning that is more effective and efficient and according to the needs of students, it will make students feel happy in the learning process, especially history lessons. Based on the limitations of history learning media at SMA Kartikatama Metro, it is one of the obstacles that makes students less interested in learning, thereby reducingstudents' understanding in learning history. The purpose of this research was to produce local history learning media based on Metro colonization visualization. Learning media are developed in accordance with the systematics and standards of visualization eligibility criteria. The research method used is Sugiono level 1 Research and Development, where this development research makes products without testing them in the field externally. The results of this development research in the form of learning media based on Metro colonization visualization as a support for the learning process of local history at SMA Kartikatama Metro have been declared feasible and can be tested for class XI students of SMA Kartikatama Metro. The product developed is declared feasible after going through the material and design expert validation stage where the final percentage of material experts gets 93.3% and the final percentage of design experts gets 88.6% or in the